Niveles de calcio en la calidad del huevo de codorniz (coturnixcoturnix japónica) en Santo Domingo de los Tsáchilas - Quintanilla García, José Rigoberto (2012)
This research joins soi led out at the Cerro secteur of Bomboli, sights of the city, located fr Victor Manuel Lopez Cooperative. Province of Santo Domingo de los Tsáchilas, canton Saint-Domingue, whose geographical location is 0 ° 14 '20''south latitude and 79 º 15 'west longitude 13''de, joins a height of 655 m d'altitude, with a duration of 90 days, the objects). To evaluate the effect of calcium levels in Food quail (Coturnix coturnix japonica) in the stance phase b). Determine the contribution of five levels of l'inclusion of calcium on the quality of the quail egg shell. C). The cost-effectiveness of treatments Set fr study. The effect of five different calcium levels T1 = 2.8% calcium balance. T2 = 3.3% calcium balance. T3 = 3.8% calcium balance. T4 = 4.3% calcium balance. T5 = 4.8% calcium balance. Were used: 200 quails were distributed the same fr five treatments with four replicates with 10 quails per experimental unit, SE used Completely Randomized Design with five treatments and four repetitions. To determine statistical differences among the treatments used to mediate the test Tukey Multiple ranges (eg ≥ 0.05%) of statistical probability. Treatments base fr five doses of calcium in the response of quail egg production ne statistical differences in food consumption, food consumption was reported maire the treatment of calcium 3.3% 2184.23 g, what de l'UN representants of 26.00 g food intake / animal/dia-1. The largest number of eggs was reported by 3.3% calcium supplied with eggs 742,. The better response of egg weight obtained by applying the 4.3% to 11.22 g calcium, and Major in the thickness of the eggshell of quail reported to provide 4.8. 0.031% of calcium, the best Quail Egg structure with the addition of calcium from 3.3% to 42.55% with food ration of yolk, albumin 48.14% 9.31% and shell.